Knowledge, awareness and readiness of private sector doctors practising in the Ethekweni and Ugu districts of KwaZulu-Natal province for the implementation of the National Health Insurance - S. Latiff-Khamissa; Panjasaram Naidoo (South African Family Practice)
Background: The proposed National Health Insurance (NHI) aims to improve quality of care and equity in healthcare financing for all South Africans. Successful implementation requires participation by stakeholders, such as private sector doctors who play an important role in healthcare delivery. A study was conducted to determine their knowledge, awareness and readiness for the implementation of the NHI.